Analysing the interplay of environmental virology, public health, and sanitation: a comprehensive review from a Kenyan perspective - Opere, Michael Wasonga (Frontiers in Cellular and Infection Microbiology, 2023)
This comprehensive review examines the interplay between environmental virology, public health, and sanitation in the unique context of Kenya. The review sheds light on the specific viral threats faced by the country, including waterborne viruses, zoonotic infections, and emerging viral diseases, and their implications for public health. It explores the prevailing public health challenges in Kenya associated with environmental viromics, such as infectious viral diseases, and the rising burden of other infectious particles. The role of sanitation in mitigating viral infections is highlighted, emphasising the importance of clean water supply, proper waste management, and hygienic practises. The review also presents strategies for strengthening environmental virology research in Kenya, including enhancing laboratory capacities and leveraging technological advancements. Furthermore, the policy implications and recommendations derived from the review emphasise the need for multi-sectoral collaboration, evidence-based decision-making, and long-term investments in infrastructure and behaviour change interventions. Implementing these strategies can enhance the understanding of environmental virology, improve public health outcomes, and ensure sustainable sanitation practises in Kenya, ultimately contributing to the well-being of the population and sustainable development.